A Review on Antimicrobial Assessment of Coumarin-Based Compounds - Yadav, Anand Kumar; B.K., Krishna Bahadur (Cognition, 2026)
Coumarins are a frequent component of many medicinal plants like tonka bean, bitter orange, cinnamon, clover, bilberry, peaches, and plums and are members of the benzopyrone family. Various pharmacological activities have been shown by natural and synthetic coumarins. The significant pharmacological variety of coumarins is being used for the treatment of infectious diseases, cardiovascular disorders, inflammation, neurodegenerative disorders, and cancer. These advantages for human health are due to the substantial structural variation of coumarins. Their antibacterial properties were initially discovered in 1945 and found that they could inhibit the growth of different bacterial strains. Bioavailability is the absorption of a drug from the digestive system after the oral dose is administered. Coumarins prevent the growth or kill the microbes through various modes of action. Every year, invasive infections caused by human fungal pathogens claim the lives of more than a million people, making them covert killers. To effectively prevent or cure life-threatening fungal illnesses, however, research in this area has not advanced quickly enough. Natural and synthetic coumarins show effective inhibition of gram-positive and Gram-negative bacterial strains, fungi, and viruses. This special issue’s goals of study are to summarize the current research on coumarin derivatives, their antibacterial and antifungal properties, and to offer suggestions for further study in the area. The current study provides an overview of coumarins’ biological capabilities, availability, and origin while also taking into account the key mechanisms underlying their therapeutic effects. Natural coumarins such as umbelliferone, esculetin have good antimicrobial activities. But most of the synthetic coumarin derivatives exhibited excellent antimicrobial properties.